Rancang dan bangun perangkat pencatat waktu pada olahraga roller skating cepat berbasis RFID - Himawanto, Wasis; Sanjaya, Ardi; Wijanarko, Bambang (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Sports that require speed for the Athlete to reach the finish line with the fastest time will be the winner in a speed skating race. With the demand to recap the speed of the alet entering the finish line, it is necessary to calculate the time that can be used in a speed skate race. Tools such as stopwatches have been used without weaknesses in the device, but weaknesses often arise from human error and result in many athletes being harmed. So we need a tool that can record athletes' speed without any errors so that athletes' speed can be recorded. This research aims to develop a speed-measuring instrument by utilizing radio signals or RFID to minimize human error in the race. This research uses research development methods (Research and Development). The timekeeper uses an identity tag attached to the skate and a sensor reader (Tag Reader) to detect the time. The study results show that RFID for recording time in roller skates is already valid and feasible. The development of this tool RFID, RFID, can detect the identity of the time between the Tag and Tag Reader with a maximum distance of 3m. Using this tool can improve the ability to record time in roller skating to record the time produced by athletes when reaching the finish. The use of this tool is practical and easy, so it is in accordance with the regulations in roller skating and as needed in the sport. The timing system will work when the Tag passes the Tag Reader attached to the start/finish line in a speed skating race.